Securing Australia's future in the Indo-Pacific - Rumley, Dennis (2023)
This paper critically reviews Australia’s recent Defence Strategic Review [DSR] and shows that its primary orientation is one of conflict rather than cooperation. It analyses the new strategic regional environment and argues that the DSR exhibits insufficient appreciation of both the region’s geopolitical nuances and its historical basis. It evaluates the question in the negative as to whether China is a security threat to Australia since the DSR implies the opposite to be the case. It discusses the ongoing problems that the Australian security community has had in coming to terms with an indigenous and sustained regional security narrative and shows that the DSR has come up with yet another version of Australia’s Indo-Pacific. The paper then evaluates the debate over the “rules-based order” and suggests that this is not necessarily in the interests of all regional states, including Australia. It discusses the benefits and limitations of Australia’s current security alliances and concludes that the present structure, reinforced by the DSR, does not adequately meet Australia’s security needs. Finally, the paper outlines a series of strategies that need to be carefully considered as part of the development of a new Australian Indo-Pacific security narrative designed to maximise national and regional security.